The Effects of Furosemide on Behavioral and Hormonal Parameters in Male and Female Mice Subjected to Immobilization and Cold-Water Stress - Al Za'abi M; Ali BH; Al Suleimani Y; Al-Zakwani I; Al-Fulaiti B; Manoj P; Nemmar A (Dove Medical Press, 2021)
Mohammed Al Za'abi,1 Badreldin H Ali,1 Yousuf Al Suleimani,1 Ibrahim Al-Zakwani,1 Balqees Al-Fulaiti,1 Priyadarsini Manoj,1 Abderrahim Nemmar2 1Department of Pharmacology and Clinical Pharmacy, College of Medicine and Health Sciences, Sultan Qaboos University, Muscat, Oman; 2Department of Physiology, College of Medicine and Health Sciences, UAE University, Al Ain, United Arab EmiratesCorrespondence: Mohammed Al Za'abiDepartment of Pharmacology, College of Medicine and Health Sciences, Sultan Qaboos University, P. O. Box 35 Al Khoud, Muscat, 123, OmanEmail zaabi@squ.edu.omIntroduction: The diuretic agent furosemide (FUR, 25 and 50 mg/kg) has been shown in a single report to act as an anti-stressor agent in two models of acute stress in mice, viz. electric foot-shock stress and immobilization (IMS). The present work aimed to investigate the possible anti-stressor action of FUR on two models of acute stress in mice, cold-water stress (CWS) and IMS, and tried to determine whether gender has any impact on the effect of FUR.Methods: FUR (40 mg/kg) was injected intraperitoneally, and after 30 minutes, mice were subjected to CWS (4°C for three minutes) or IMS (fixing movement for two and a half hrs using adhesive tape). Motor and exploratory activities, neuromuscular coordination, and thermal nociception were then tested. Blood was collected from the mice and used to measure the concentrations of three stress hormones (corticosterone, epinephrine and prolactin).Results: Mice subjected to CWS and IMS had significantly reduced motor and exploratory activities, neuromuscular coordination, and increased nociception. CWS and IMS also significantly increased the plasma concentrations of the three hormones. FUR pretreatment significantly mitigated these stress-induced hormonal changes. There was no significant sex difference when CWS or IMS was applied.Discussion: IMS and CWS stimuli in male and female mice caused significant elevations in the plasma concentrations of corticosterone, epinephrine, and prolactin, accompanied by a significant reduction of motor and exploratory activities, neuromuscular coordination, and thermal nociception. There were no sex differences when IMS was applied. In stressed mice, prior administration of FUR (40 mg/kg) significantly decreased the concentrations of stress hormones, and this effect significantly mitigated the stress-induced behavioural and motor changes.Keywords: furosemide, immobilization stress, cold-water stress, corticosterone, prolactin, epinephrine